Structural and Functional Insights into a Lysine Deacylase in the Cyanobacterium Synechococcus sp. PCC 7002 - Liu, Xin (Plant Physiol, 2020)
Lys deacylases are essential regulators of cell biology in many contexts. Here, we have identified CddA (cyanobacterial deacetylase/depropionylase), a Lys deacylase enzyme expressed in the cyanobacterium Synechococcus sp. PCC 7002 that has both deacetylase and depropionylase activity. Loss of the gene cddA led to slower growth and impaired linear and cyclic photosynthetic electron transfer. We determined the crystal structure of this depropionylase/deacetylase at 2.1 Å resolution and established that it has a unique and characteristically folded α/β structure. We detected an acyl binding site within CddA via site-directed mutagenesis and demonstrated that this site is essential for the deproprionylase activity of this enzyme. Through a proteomic approach, we identified a total of 598 Lys residues across 382 proteins that were capable of undergoing propionylation. These propionylated proteins were highly enriched for photosynthetic and metabolic functionality. We additionally demonstrated that CddA was capable of catalyzing in vivo and in vitro Lys depropionylation and deacetylation of Fru-1,6-bisphosphatase, thereby regulating its enzymatic activity. Our identification of a Lys deacylase provides insight into the mechanisms globally regulating photosynthesis and carbon metabolism in cyanobacteria and potentially in other photosynthetic organisms as well.